Recurrence of particles in static and time varying oval billiards - Leonel, Edson Denis [UNESP]; Dettmann, Carl P. (Elsevier B.V., 2012)
Dynamical properties are studied for escaping particles, injected through a hole in an oval billiard. The dynamics is considered for both static and periodically moving boundaries. For the static boundary, two different decays for the recurrence time distribution were observed after exponential decay for short times: A changeover to: (i) power law or; (ii) stretched exponential. Both slower decays are due to sticky orbits trapped near KAM islands, with the stretched exponential apparently associated with a single group of large islands. For time dependent case, survival probability leads to the conclusion that sticky orbits are less evident compared with the static case. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Billiards; Escape of particles; Fermi acceleration